Private Voluntary Organizations in Egypt: Islamic Development, Private Initiative, and State Control Denis J. Sullivan. Gainesville, FL: University of Florida Press, 1994. (American Journal of Islam and Society, 1996)
Over the past five years or so, the considerable western interest inthe role played by nongovernmental voluntary associations in Egypt hasbeen reflected in a growing English-language literature on the subject.Researchers tackle the question from a range of perspectives.One approach, relatively state-centered and legalistic, focuses on howCairo manages to control, co-opt, or "corporatize" autonomous organizationsincluding labor and professional syndicates, agricultural and othercooperatives, and private not-for-profit groups. The principle tool for reiningin private voluntary and community associations is the notorious Law32 of 1964. Under Law 32, the Ministry of Social Affairs can interferedirectly in all aspect of associational life-articulation of goals, election ofofficers, pursuit of projects, allocation of funds, and so on. Among the wellknownsecular nonprofit groups with international linkages that have beendenied licenses from the Ministry are the Egyptian Organization of HumanRights and the Arab Women's Solidarity Association. In this legal and policymilieu, many scholars and human rights activists argue that no registeredassociation in Egypt can properly be deemed "nongovernmental."Other analysts, however, accept Cairo's position that the threat of radicalIslam justifies authoritarian restrictions on independent organizations.The second group of studies is inspired partly by these concerns over theradicalization of Islamist associations. Scholars familiar with social, economic, and political circumstances in the Nile Valley usually try to counteracthysterical mass media portraits of "Muslim terrorists" with inquiries intothe structure, function, membership, activities, and ideologies of a range ofIslamist institutions including welfare and charitable associations. The particularstrength of politicized Islam in the 1990s, this research suggests, restson the capacity of Islamist charities to provide a crucial layer of social servicesto a burgeoning, underemployed, increasingly impoverished population.Opinion is divided, however, on the question of whether this circumstancefavors containment and stability or frustration and insurrection.A third set of studies, sometimes overlooked by scholars, comes fromwithin the Cairo-based donor community, the "development practitioners" ...